Educational Policies and Migrations. Lessons in Contexts of Advanced Neo-liberalism - Jiménez Vargas, Felipe. (Pontificia Universidad Javeriana, 2022)
We present the results of a study of schools with a large number of foreign students. Set in the framework of an educational system characterized by a model of advanced neo-liberalism, this study uses qualitative techniques like participant observation, shadowing, the analysis of documents and interviews, and points to a group of adaptive practices of resistance, which give rise to three shifts which clash with the mandates of the model: an affective shift, a collaborative shift and a localist shift. Our findings highlight the role of teachers in implementing educational inclusion. This study also discusses the role which diversity plays nowadays in the structure of schools.
Políticas educativas y migración. Lecciones en contextos de neoliberalismo avanzado
Keywords: Immigration; Política educativa; Investigación empírica; Educación multicultural